The Effect of Investment Opportunity Set on Financial Performance and Share Price in Property and Real Estate Companies Listed on IDX - Khaela Febrianti; Hartanto Rianto; Khania Br Tarigan; M. Syauqi Anwar; Redika Pasaribu (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This study aims to investigate the impact of Earnings Per Share (EPS), Market to Book Value of Assets (MBVA), Market to Book Value of Equity (MBVE), Capital Expenditure to Book Value Asset Ratio (CEP/BVA), and Capital Expenditure to Market Value of Assets Ratio (CEP/MVA) on the financial performance and stock prices of Property and Real Estate Companies listed on the IDX (Indonesia Stock Exchange). The data utilized for this study are annual reports obtained from each company, accessible on the website www.idx.go.id. The research employs the associative method with statistical analysis and panel data testing. The sampling method employed is purposive sampling, encompassing a total sample of 10 Property Companies listed on the IDX, and the data spans from 2016 to 2022. The study's findings reveal that Earnings Per Share (EPS), Market to Book Value of Assets (MBVA), Market to Book Value of Equity (MBVE), Capital Expenditure to Book Value Asset Ratio (CEP/BVA), and Capital Expenditure to Market Value of Assets Ratio (CEP/MVA) exert a positive and significant influence on the financial performance and stock prices of Property and Real Estate Companies listed on the IDX.